2012
DOI: 10.7861/clinmedicine.12-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Teaching medical professionalism

Abstract: -Medical professionalism has been notoriously difficult to define and remains poorly understood. Because of this, graduates often have contrasting views on how it is best taught. These views should be considered and incorporated into teaching methods in order to enhance learning and development. Over a six-month consecutive period doctors and medical students in County Durham and Darlington Foundation Trust completed a questionnaire asking them to define professionalism, state where they felt they had learnt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 5 publications
2
37
0
1
Order By: Relevance
“…Majority of students Govindaraja C, Ramachandran G, Ko Ko Min A MedEdPublish https://doi.org/10.15694/mep.2016.000097 in both years preferred learning professionalism by role modeling by teachers as the first choice followed by case studies, lecturers and movies which is in line with the findings of prior research (Akhund et al, 2014;Byszewski et al, 2012;S. R. Cruess et al, 2008;Morreale, Balon, & Arfken, 2011;Ratanawongsa et al, 2006;Riley & Kumar, 2012;Weissmann, Branch, Gracey, Haidet, & Frankel, 2006). Students imbibe professional values from the culture of the learning environment, (Mann, 2011) the teachers, peers and hospital patients to practice in the community, evolving with time, in their professional journey (Johnston, 2006).…”
Section: Higher Integrity Displayed By Staff Than Medical Studentssupporting
confidence: 76%
“…Majority of students Govindaraja C, Ramachandran G, Ko Ko Min A MedEdPublish https://doi.org/10.15694/mep.2016.000097 in both years preferred learning professionalism by role modeling by teachers as the first choice followed by case studies, lecturers and movies which is in line with the findings of prior research (Akhund et al, 2014;Byszewski et al, 2012;S. R. Cruess et al, 2008;Morreale, Balon, & Arfken, 2011;Ratanawongsa et al, 2006;Riley & Kumar, 2012;Weissmann, Branch, Gracey, Haidet, & Frankel, 2006). Students imbibe professional values from the culture of the learning environment, (Mann, 2011) the teachers, peers and hospital patients to practice in the community, evolving with time, in their professional journey (Johnston, 2006).…”
Section: Higher Integrity Displayed By Staff Than Medical Studentssupporting
confidence: 76%
“…This data has similarity with other studies (Salam et al, 2012b;Swick, 2000). Scholars identified that professionalism is easy to recognize but notoriously difficult to define and poorly understood (Riley and Kumar, 2012;Swick, 2000). This is the place where faculty member must get in to make a clear understanding and prepare students to practice on fundamental concerns of humanistic characteristics of professionalism.…”
Section: Discussionmentioning
confidence: 78%
“…Role models and learning through experience were identified as being the most useful sources for teaching professionalism whereas lectures and online teaching were not felt by many to be valuable resource (Riley S & Kumar N. 2012). In our study students considered observing and modelling and individual mentoring as best teaching strategy while faculty considered Including in evaluation and Observing and modeling as important teaching tools for professionalism and formal teaching was not considered important by both faculty and students.…”
Section: Discussionmentioning
confidence: 99%
“…According to the doctors and medical students in County Durham and Darlington Foundation Trust Role models and learning through experience were identified as being the most useful sources for teaching professionalism whereas lectures and online teaching were not felt by many to be valuable resources (Riley S & Kumar N. 2012). Teaching of professionalism should integrate with difficulties of medical practice to overcome the apparent strains among medical students (Cuesta-Briand B et al 2014).…”
Section: Research Articlementioning
confidence: 99%